2018
DOI: 10.3390/ph11040101
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-1 (COX-1) and COX-1 Inhibitors in Cancer: A Review of Oncology and Medicinal Chemistry Literature

Abstract: Prostaglandins and thromboxane are lipid signaling molecules deriving from arachidonic acid by the action of the cyclooxygenase isoenzymes COX-1 and COX-2. The role of cyclooxygenases (particularly COX-2) and prostaglandins (particularly PGE2) in cancer-related inflammation has been extensively investigated. In contrast, COX-1 has received less attention, although its expression increases in several human cancers and a pathogenetic role emerges from experimental models. COX-1 and COX-2 isoforms seem to operate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
115
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(126 citation statements)
references
References 173 publications
2
115
0
Order By: Relevance
“…Hence, the inhibitory activity of ellagic acid on both COX1 and COX2 may be associated with the anti-invasive activity in these systems. Although COX1 has long been considered to be constitutively expressed in all tissues and linked to normal physiological functions, not to pathological ones, several recent studies have reported that COX1 can also be upregulated in various pathological conditions and associated with inflammation and cancer [43,44]. Next, we evaluated other genes potentially involved in anti-invasive activity of ellagic acid under acidic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the inhibitory activity of ellagic acid on both COX1 and COX2 may be associated with the anti-invasive activity in these systems. Although COX1 has long been considered to be constitutively expressed in all tissues and linked to normal physiological functions, not to pathological ones, several recent studies have reported that COX1 can also be upregulated in various pathological conditions and associated with inflammation and cancer [43,44]. Next, we evaluated other genes potentially involved in anti-invasive activity of ellagic acid under acidic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is that increased heme synthesis in tumors is intended to support the activity of specific hemoproteins. Cells are equipped with several hemoproteins (69) and for some of them a role in cancer has been reported, including myoglobin (70), tryptophan 2,3-dioxygenase (TDO) and indoleamine-2,3-dioxygenase 1 and 2 (IDO1/2) (71-73), mitochondrial cytochromes (74, 75), cytochrome P450 (76, 77), and cyclooxygenases (78,79). Studies on lung cancer demonstrated that the amount of oxygen-utilizing hemoproteins, such as cytoglobin, cytochrome c, cytochrome P450 family 1 subfamily B member 1 (CYP1B1) and prostaglandinendoperoxide synthase 2 (COX2) are higher in tumor cells as compared to normal cells and that, at least for cytoglobin and cytochrome c, their levels depend on the rate of heme synthesis and cellular heme content (46).…”
Section: Heme Synthesis and Cancermentioning
confidence: 99%
“…Triggering a fibrotic tissue process by the sulfidopeptide LT stimulated fibroblasts only when simultaneously PG synthesis was suppressed by indomethacin [458]. Detailed knowledge of various pathways with its functional implications is needed and "…metabolic network by using systems biology approaches, should be strongly encouraged" [459]. Furthermore, this needs to include reaction specifity information of regulatory mediators impacting the biological activity of various enzymes and poteins including its dynamic changes [460][461][462][463].…”
Section: Summary (Fig 4)mentioning
confidence: 99%